Recognition Memory of Vocabulary (RMV) and Reading Comprehension for EFL Learners in A Pesantren-Based Junior Secondary School - Hari Prastyo; Agustin Pramita Dewi; Ali Mohammed Saleh Al-Hamzi; Ndishunwani Vincent Demana; Siti Khikmiyah; Aida Fitrianah Zen (Indonesian Journal of EFL and Linguistics, 2026)
This research investigates the correlation between recognition memory of vocabulary (RMV) and reading comprehension among eighth-grade English as a Foreign Language (EFL) learners at MTs Favorit Darut Taqwa Dlanggu, Indonesia. Utilizing a mixed-methods research design combining quantitative correlational analysis and qualitative descriptive inquiry, the study engaged 28 participants selected through purposive sampling based on their educational level and prior learning experiences. Data collection was executed through two distinct instruments: a vocabulary recognition memory assessment comprising multiple-choice questions and a reading comprehension evaluation. The findings indicated a statistically significant and exceptionally strong positive correlation between vocabulary recognition memory and reading comprehension (r = 0.976, p < 0.01), thereby illustrating a robust connection between learners’ capacity to recognize previously acquired vocabulary and their performance in comprehension tasks. Nonetheless, the results also imply that vocabulary recognition in isolation does not comprehensively account for reading comprehension, as various reading strategies, including skimming, scanning, and inference-making, were also integral to the students’ comprehension processes. This study underscores the pedagogical significance of amalgamating contextualized vocabulary instruction with explicit training in reading strategies and differentiated instructional methods. The implications of these findings offer valuable pedagogical insights aimed at enhancing English literacy instruction within EFL environments, particularly in Pesantren-based educational institutions.